2011
DOI: 10.1080/19338244.2010.539639
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Work Stress on Burnout and Quality of Life Between Female Nurses and Female Doctors

Abstract: The objective of this study was to compare the effect of work stress on job burnout and quality of life between female nurses and doctors in China. The participants were 947 female nurses and 685 female doctors selected from Fujian provinces by using stratified cluster sampling method. The Chinese version of Short Form-36 Health Survey was used to measure quality of life; the Occupation Stress Inventory-Revised Edition was applied for occupational stress; and the Maslach Burnout Inventory-General Survey was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 19 publications
5
48
1
1
Order By: Relevance
“…Similarly low smoking rates among female doctors, as compared with their male counterparts, have been recently reported in China. 18 A plot of reported smoking rates from all studies (Figure 1) clearly demonstrates the magnitude of this decline in Japan, which is consistent with trends in many other countries. For example, the earliest large-scale reviews of doctors’ smoking habits appear to have been undertaken by Adriaanse and colleagues, 8 , 19 who found that smoking prevalence rates had declined substantially in many countries since the 1950s.…”
Section: Resultssupporting
confidence: 77%
“…Similarly low smoking rates among female doctors, as compared with their male counterparts, have been recently reported in China. 18 A plot of reported smoking rates from all studies (Figure 1) clearly demonstrates the magnitude of this decline in Japan, which is consistent with trends in many other countries. For example, the earliest large-scale reviews of doctors’ smoking habits appear to have been undertaken by Adriaanse and colleagues, 8 , 19 who found that smoking prevalence rates had declined substantially in many countries since the 1950s.…”
Section: Resultssupporting
confidence: 77%
“…Psychosocial work factors such as skill level, job strain, work‐life balance, psychological job demand, decision latitude, decision authority and job control can also influence QoL. Psychosocial work factors as a whole affected the QoL of male Malaysian automotive factory workers (Edimansyah, Rusli, Naing, Mohamed, & Winn, ); other studies linked QoL with specific aspects, such as job strain (Lerner, Levine, Malspeis, & D'Agostino, ; Tzeng, Chung, & Yang, ), job control (Liang, Hsieh, Lin, & Chen, ), social support (Jönsson, ; Liang et al., ; Tzeng et al., ), work‐life imbalance (Makabe, Takagai, Asanuma, Ohtomo, & Kimura, ), occupational stress and role overload (Wu, Li, Wang, Yang, & Qiu, ) and imbalanced effort/reward (Teles et al., ). However, promotion of work ability can benefit QoL in physical, psychosocial, social relationship and environmental domains (Milosevic et al., ; Sörensen et al., ) and positive correlations between QoL domains and job satisfactions have also been revealed (Cimete, Gencalp, & Keskin, ; Ibrahim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…6 Other research shows that job satisfaction is the strongest predictor of nurses' commitment to a specific hospital 7 and that job satisfaction is connected to occupational stress in nursing. 8 Occupational stress is a serious problem affecting nurses 9 and research shows that this is connected with absence from work 1 and intentions to quit a hospital. 8 Inductionsparticularly those connected with mental health -have the potential to help nurses cope with challenging workplace experiences and to self-reflect about their own cognitive responses at work.…”
Section: Introductionmentioning
confidence: 99%